Thermal spray and laser cladding of nickel-chromium coatings for high temperature applications - Song, Bo (2018)
To reduce the environmental impact, there is a trend for the thermal power generation industry to increase the usage of the biomass fuel. However, the severe corrosion of boiler materials that is brought about by the high chlorine and alkaline content in the biomass limits the application of biomass fuel and the operation temperature of the biomass boiler. NiCr based alloys that have high Cr content are an ideal solution to combat this problem; they can protect the boiler steel substrate from the chlorine-induced corrosion. There are quite a lot of coating deposition techniques, but the most suitable one for the deposition of Ni50Cr alloy on the boiler material and thereby provides satisfactory protection is still in debate. The major aims of this research included: determining the most suitable coating deposition technique for high temperature oxidation/corrosion applications of NiCr alloys in four candidates (high velocity oxygen liquid/gas fuel (HVOLF/HVOGF) thermal, cold spray and laser cladding); describing and explaining the high temperature oxidation/corrosion performance of coatings deposited using shortlisted deposition routine. The key objectives of this research were: a literature review that can identify the knowledge gap existing in the current research of high temperature oxidation/corrosion NiCr-based coatings; successful deposition of NiCr-based coatings using techniques include in this study, and the deposition product should be of satisfactory quality; high temperature oxidation/corrosion exposure of deposited coatings in test rigs; comprehensive summary of the oxidation/corrosion behaviours of coatings and identification of possible mechanism to explain these behaviours; direction for the future development of high temperature NiCr-based corrosion resistance coatings. To achieve abovementioned objectives, following work were conducted. Short-term air thermogravimetric analysis (TGA) results of as-sprayed HVOF coatings were used to determine the air oxidation resistance of the five HVOF thermal sprayed coatings. The HVOLF and HVOGF coatings that had better air oxidation resistance were hypothesized to have better steam oxidation and fireside corrosion performance and shortlisted for the subsequent high temperature test in various atmospheres. There was no recommended process parameter sets for the laser cladding of the Ni50Cr powder. Therefore, a process window was built to help decide the most suitable parameter set. Laser cladded coating that had satisfactory metallurgical quality, acceptable thickness, maximum width and minimum dilution was selected as the candidate for subsequent high temperature exposure. The optimization process of the laser cladding parameter had been published and was not included in this thesis. The cold sprayed coating was deposited by using the Xi’an Jiaotong University’s custom-made cold spray set-up. The microstructure of the deposited cold sprayed coating was acceptable after grinding several top layers of the coating (~ 500 μm), and the coating was placed into the high temperature test rigs for the further investigation of the high temperature oxidation/performance of cold sprayed coating. Longer-term air oxidation (compared with the TGA dwell time), steam oxidation and chlorine-induced fireside corrosion tests of four coatings were conducted in the simulation test rigs built in our laboratory. Following procedures were adopted to investigate the oxidation/corrosion behaviour. In the case of the air oxidation test, three samples of each coating were placed into the high temperature box furnace and was removed from the furnace after 1 h, 10 h and 100 h of exposure time, in succession. In the case of the steam oxidation test, four samples of each coating were sent into the test rig and collected after 250 h, 500 h, 750 h and 1000 h of exposure time one after another. While in the case of the chlorine-induced fireside corrosion test, two samples, with KCl and without KCl deposit on the surface of coating, were the candidates of the 250 h high temperature corrosion exposure. Adopting a relative short exposure time in the chlorine-induced corrosion test was owing to the severe attack ability of chlorine and alkali metal on material. Specimens, after the high temperature oxidation/corrosion and collected at the specific time points, can provide valuable information about the evolution of the air oxidation, steam oxidation and fireside corrosion behaviour of four coatings. Several material characterisation methods such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) were used to obtain the said information. By conducting the abovementioned experiments and analysing the obtained results, the rank of the oxidation/ corrosion resistance of four coatings in various atmospheres at high temperature can be asserted. The mechanism behind the different oxidation/corrosion behaviour for various coatings can be investigated and several possible mechanisms that can explain the observed results are adopted. Finally, a promising Ni50Cr coating deposition method – HOVLF and laser cladding is recommended.